STUDY ON RIGOR MORTIS SCALE DEVELOPMENT AND PINK GLASS PARADOX AS A NEW CONCEPT IN LITERATURE - Ömer Okan FETTAHLIOĞLU (Fırat University, 2019)
Overall objective of this study is to create a process explaining the relationships between concepts which we thought it was related to each other in the literature and interpret this process. Especially, the concepts used in this study that the Business Analysis, Enviromental Analysis, Proactive and Reactive Approaches, Entropy- Negative Entropy and Rigor Mortis were investigated. Literature studies on these concepts were reviewed. The process which showing the relationship between these concepts and supported the literature has been prepared and interpreted by us. Definition of ‘’Pink Glass’’ and ‘’Clear Vision’’ paradoxes in this process, not previously used, was made according to the literature.